THE RELATIONSHIP BETWEEN PARENTAL COMMUNICATION AND EMOTIONAL REGULATION IN ADOLESCENTS AGED 13-15 YEARS: A STUDY AT MTS AL KHOLAFIYAH TEKUNG,LUMAJANG REGENCY - Ike Nia Permata Bunda; Tutik Hidayati; Sri wahyuningsih (The Shine Cahaya Dunia Kebidanan, 2026)
Background: Adolescents aged 13–15 years are in a phase of rapid emotional development, requiring strong emotional regulation skills to avoid risky behavior. Warm, open, and responsive parental communication is a crucial factor in helping adolescents understand and manage their emotions more healthily. However, poor communication within the family often leads to adolescents experiencing difficulty regulating their emotions. With this background in mind, the researcher aimed to explore the "Relationship Between Parental Communication and Emotional Regulation in Adolescents Aged 13–15 Years at MTS Al Kholafiyah Tekung, Lumajang Regency." Method: The research design is a plan or plan created by the researcher as a framework for the activities to be implemented. This study employed a cross-sectional design. Results: The results of the rho test indicated a p-value of 0.00 with a significance level (α) <0.05. Because the p-value is less than α, H₀ is rejected and H₁ is accepted. This indicates a relationship between parental communication and emotional regulation in adolescents aged 13-15 years. A study at MTS Al Kholafiyah Tekung, Lumajang Regency. Conclusion: The results of this study indicate a relationship between parental communication and emotional regulation in adolescents aged 13-15 years. A study at MTS Al Kholafiyah Tekung, Lumajang Regency.